Zbirka tapiserij v palači grofov Attems v Gradcu - Komić Marn, Renata (Acta historiae artis Slovenica, 2025)
The article presents new data and findings on the collection of tapestries kept by the Counts of Attems in their palace in Graz until the early 1960s. The current whereabouts of the majority of these tapestries are unknown. Based on an analysis of the individual, constantly changing contexts and the developmental dynamics of the art and other collections in the Palais Attems as well as the individual preferences and desires of the individual owners, the study focuses on establishing the identity of the commissioners or owners of the tapestries and on reconstructing the contexts of their installation in different periods. The analysis of the individual tapestries, of which photographic images are presented for the first time, is limited to tapestries created in the 17th century, though the research questions relate to the entire collection of tapestries of the Counts of Attems.
Keywords: art collections; Attems; baročne tapiserije; Baroque tapestries; Fideikommiss; fidejkomis; museum collections; muzejske zbirke; palača Attems (Gradec, Avstrija); Palais Attems (Graz, Austria); tapestry collections; tapiserije; umetnostne zbirke